Algunos estudios de alelopatia de Rumex crispus L. y Polygonum segetum HBK., en colombia - Gomez C.=700 1 Arango, R.; Arevalo, L.P.; Delgado, C.; Guzman, M.R.; Leon, S.M.; Marentes, D.; Correa, E.M.; Vargas, S.
(En, Es)
ilus., 13 ref.
Keywords: ALELOPATIA; RUMEX; POLYGONACEAE; METABOLISMO; FLAVONOIDES; TERPENOIDES; SESQUITERPENOS; CELULAS; DISPERSION; COLOMBIA